Plan estratégico para la Asociación de Participación Social “27 De Febrero” Productora y Comercializadora de Lácteos De La Parroquia Gualel - Tene Angamarca, Cruzcaya T (2016)
Currently in enterprises, the implementation of a strategic plan has become very important because of the great need to improve the performance of the activities managers who venture to succeed. On the other hand the uncertainty generated by the rapid changes in the economic, social, political, technological and environmental fields; they make managers effective tools rest on the strategic plan. For such circumstances this thesis general objective: "DEVELOP A STRATEGIC PLAN FOR ASSOCIATION OF SOCIAL PARTICIPATION" February 27 "PRODUCER AND DISTRIBUTOR OF DAIRY PARISH GUALEL" to achieve sustained development of the organization "of so as to enable increased participation in the local market. To achieve the goal two methods, techniques and tools for collecting information which was served for the elaboration of the thesis was used. The methods applied are: the deductive and inductive method; they develop research that allowed through a logical process. Different techniques and instruments to collect information, such as direct observation was also used the interview to the legal representative of the Association and the sample to 253 customers; who with their answers allowed us to detect internal problems of the Association and to perform external analysis (PEST and Porter's 5 Forces) was known of the problems affecting the company to. The results of the research are: to perform external analysis was determined in the political factor there are entities that regulate the production Dairy Association, within the economic factor the purchasing power of the inhabitants of the Gualel parish is low, socially it is that unemployment and underemployment in the parish affects purchasing power and finally the technology sector currently there are technologies that contribute to improve processes and have better benefits for the Association. In the competitive analysis it was completed which there competition for the Association is offering better quality products. And finally in the internal analysis of the company detected various shortcomings, the Association is administered in an empirical way, its organizational structure is not well defined, is deficient in training partners, besides the products are not quality which the Association can not position in the market against the competition by offering their products to the final consumer. It is concluded that the Association has an empirical administration also does not have a business philosophy and organizational structure, also lacks carry out promotional and advertising programs to raise awareness of both the company and the existence of the Association. It is recommended to implement the strategic plan developed which serve as a great contribution to the company to implement, plus an analysis of the changes that may be made to meet customer expectations. Finally the total budget for the implementation of these objectives amounts to $68.880,00, value that will be financed entirely by the Association.